Vietininkiniai būdvardžiai – archajinė senųjų raštų posesyvumo raiškos priemonė - Maskuliūnas, Bronius (Baltistica, 2000)
LOCATIVE ADJECTIVES – A SPECIFIC ARCHAIC FORM EXPRESSING POSSESSION IN OLD LITHUANIAN WRITINGS The paper deals with a construction expressing possession encountered in Old Lithuanian writings. In this construction a noun in the locative forms the base to which the enclitic pronoun jis is added. In most instances the adjectives under discussion describe a place or a spatial concept but there is a possessive component of meaning in their semantic structure, too. Daukša’s Postilla offers the largest number, i. e. 16 different adjectives of this kind, most frequent of which is dangujejis. This is almost the only one that occurs in other old writings. From the geography of the most frequently used adjective dangujejis we may conclude that attributives with the locative plus jis were most used by those who employed the central variant of the written language. Competition with adjectives with suffixes and especially with the genitive of the noun is the main reason for the later disappearance of attributives with the locative plus jis. In present-day Lithuanian the adjectives under discussion constitute essentially an archaic category.